2001
DOI: 10.4049/jimmunol.166.2.1241
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Is a Regulator of Monocyte-Macrophage Function

Abstract: Hepatocyte growth factor (HGF) is a potent paracrine mediator of stromal/epithelial interactions, which is secreted as a matrix-associated inactive precursor (pro-HGF) and locally activated by tightly controlled urokinase cleavage. It induces proliferation and motility in epithelial and endothelial cells, and plays a role in physiological and pathological processes involving invasive cell growth, such as angiogenesis and parenchymal regeneration. We now report that HGF induces directional migration and cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 45 publications
(43 reference statements)
6
109
0
Order By: Relevance
“…In fact, conventional inhibitors of MET-such as small tyrosine kinase inhibitors, antibodies or decoy molecules (Christensen et al, 2003;Kong-Beltran et al, 2004;Michieli et al, 2004;Petrelli et al, 2006;Smolen et al, 2006)-impair the activity of the receptor not only in tumors but also in host cells. This is critical, since MET functions have been linked also to neo-angiogenesis and host defense responses, as this oncogene is expressed in endothelial cells as well as in macrophages and in cells of the immune system (Bussolino et al, 1992;Galimi et al, 2001;Skibinski et al, 2001). Here, we show that MET silencing in cancer cells resulted in suppression of the invasive growth program in vitro, as demonstrated by cell inability to invade surrounding matrices, grow and form anchorage-independent colonies.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, conventional inhibitors of MET-such as small tyrosine kinase inhibitors, antibodies or decoy molecules (Christensen et al, 2003;Kong-Beltran et al, 2004;Michieli et al, 2004;Petrelli et al, 2006;Smolen et al, 2006)-impair the activity of the receptor not only in tumors but also in host cells. This is critical, since MET functions have been linked also to neo-angiogenesis and host defense responses, as this oncogene is expressed in endothelial cells as well as in macrophages and in cells of the immune system (Bussolino et al, 1992;Galimi et al, 2001;Skibinski et al, 2001). Here, we show that MET silencing in cancer cells resulted in suppression of the invasive growth program in vitro, as demonstrated by cell inability to invade surrounding matrices, grow and form anchorage-independent colonies.…”
Section: Discussionmentioning
confidence: 71%
“…Although both DCs and macrophages have been described to be able to express c-met (Chen et al 1996;Galimi et al 2001;Ovali et al 2000;Rutella et al 2006) However, the presence of macrophages in the CNS at the onset phase of EAE, prior to the expression of c-met on splenic macrophages contradicts such a scenario.…”
Section: Hgf and C-met Expression In Eaementioning
confidence: 68%
“…However, the function of HGF/c-met signaling in monocytes/macrophages is at present a matter of debate with, functions ranging from migration to differentiation reported (Beilmann et al 1997;Beilmann et al 2000;Chen et al 1996;Galimi et al 2001;Jiang et al 2001). Although HGF/c-met signaling may directly influence leukocyte responses in inflammation and autoimmune diseases, the mechanisms involved remain at present poorly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakai and colleagues found that human alveolar macrophages contained immunoreactive HGF, but they did not study HGF secretion by alveolar macrophages. LPS-stimulated human blood monocytes have been shown to secrete small amounts of HGF in vitro, whereas unstimulated monocytes do not (Galimi et al, 2001).…”
Section: Crestani Et Almentioning
confidence: 99%